2019
DOI: 10.1039/c9ra02738f
|View full text |Cite
|
Sign up to set email alerts
|

Self-assembly of supra-amphiphiles building block fabricated by β-cyclodextrin and adamantane-based ionic liquid

Abstract: A new adamantane-based ionic liquid, (11-(((-adamantane-1-carbonyl)oxy)undecyl)-1-methylimidazol-3-ium bromide (AD-C 11 im), was synthesized from 1-adamantanecarboxylic acid and observed that it can aggregate into micelles in aqueous solution. A number of experiments were conducted to understand the self-assembly of supra-amphiphiles building block fabricated by b-cyclodextrin (b-CD) and adamantane-based ionic liquid at diverse molar ratios. Studies revealed that host-guest interaction between the adamantane g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Zhong et al. [ 42 ] also introduced an adamantane‐based ionogel based on the host–guest interaction between β‐CD and with adamantane group. Except for cyclodextrin molecule, Ma et al.…”
Section: Mechanisms Of Ils In Regulating Nature Of Ionogelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Zhong et al. [ 42 ] also introduced an adamantane‐based ionogel based on the host–guest interaction between β‐CD and with adamantane group. Except for cyclodextrin molecule, Ma et al.…”
Section: Mechanisms Of Ils In Regulating Nature Of Ionogelsmentioning
confidence: 99%
“…This ionogel contains β-CD and an asymmetric Gemini ZIL which contains azobenzene and bis(trifluoromethanesulfonyl)imide (TFSI − ), the host-guest interaction between β-CD with photoresponsive azobenzene group and TFSI − ion can be control by regulating the photon radiation and temperature. Zhong et al [42] also introduced an adamantanebased ionogel based on the host-guest interaction between β-CD and with adamantane group. Except for cyclodextrin molecule, Ma et al [43] reported an ionogel with detectability to CO 2 based on host-guest interaction between a carbamate IL guest molecule with a bis-cyanostilbene derivative host molecule (Figure 3B).…”
Section: Host-guest Interactionmentioning
confidence: 99%
“…Hence, it has a hydrophobic inner cavity and a hydrophilic outer surface. 18 As a natural product, it is cheap, non-toxic, has good biocompatibility and excellent biodegradability and is easy to modify due to a large number of hydroxyl groups on its surface. In particular, its inner cavity can form inclusion complexes with specific pollutant molecules, so it has attracted a great deal of attention in the removal of pollutants from wastewater.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Zhong et al found spherical vesicles AD-C 11 im@1β-CD formed when the amount of β-CD was added the same as 11-(((-adamantane-1carbonyl)oxy)undecyl)-1-methylimidazol-3-iumbromide (AD-C 11 im), which was also confirmed by atomic force microscopy (AFM), dynamic light scattering (DLS), and transmission electron microscopy (TEM). 22 Shi et al discovered the formation of vesicles in the concentrated aqueous solution of 1-dodecyl-3-methylimidazolium bromide (C 12 mimBr) and β-CD and thought that it was the H-bonding between β-CD and water, β-CDs, as well as the imidazolium headgroup of C 12 mim + and water that contribute to the C 12 mimBr@β-CD selfassembly vesicle system. 23 However, as far as we know, there have never been studies on the applications of ionic liquid@β-CD vesicles in the extraction fields.…”
Section: ■ Introductionmentioning
confidence: 99%